Universally composable zero-knowledge sets. (2nd March 2012) - Xu, Haixia; Li, Hongda; Li, Bao
We define and construct universally composable (UC) Zero-Knowledge Set (ZKS) protocols. A ZKS protocol allows a prover to commit to a secret set S and prove statements of the form x ∈ S or x ∉ S without revealing any other information about S. The universal composability framework initiated by Canetti is very useful as it ensures stronger security such as concurrent composition, adaptive security and non-malleability. In this paper, we propose a UC ZKS protocol and prove its security in the random oracle model. Simultaneously, we give the negative result that a UC ZKS cannot exist in the standard model (without a random oracle). The negative result shows that the random oracle has both compression and extraction, which is a pair of paradoxical properties. To our knowledge, this is the first time this kind of property has been considered.